Teacher analysis in mathematics learning planning for class XI MA Al ikhlas tinabogan - Siti Nuralan (12 Waiheru, 2022)
The purpose of this study is (1) To determine the nature of planning the implementation of learning by teachers of mathematics subjects class XI MA. Al iklash Tinabogan (2) To find out the function of planning the implementation of learning by teachers of mathematics subjects class XI MA. Al-iklash Tinabogan (3) To find out the principle of planning the implementation of learning by teachers of mathematics subjects class XI MA. Aliklash Tinabogan (4) To find out the factors for the preparation of learning implementation planning by the teacher of mathematics subject class XI MA Al-iklash Tinabogan. This research is qualitative. Observational data collection techniques, interviews, and documentation. The data analysis technique uses domain analysis, taxonomy, componential, and cultural themes. The results of this study are the nature, functions, principles, and factors that influence the preparation of a lesson implementation plan for mathematics subjects in class XI MA. Al-Ikhlash Tinabogan. The results of the data analysis concluded that the development of a learning implementation plan for the mathematics subject of MA Al-ikhlash tinabogan, was carried out properly because the preparation had included three stages of activities, namely identification of needs, identification of competencies, and preparation of learning programs. the function of preparing a learning implementation plan for mathematics subjects MA Al-ikhlash tinabogan, namely as planning, teaching guidelines, assessment, and as a form of learning implementation, Thus, the learning implementation plan for mathematics subjects Ma Al-ikhlash tinabogan, functions to streamline the learning process following what is planned.